Pharmacokinetics considerations for gout treatments. (July 2014) - Richette, Pascal; Frazier, Aline; Bardin, Thomas
Abstract : Introduction: Patients with gout often have comorbid conditions such as renal failure, cardiovascular disease and metabolic syndrome. The presence and required treatment of these conditions can make the treatment of gout challenging. Knowledge of the pharmacokinetics of the available drugs for the management of gout is mandatory. Areas covered: A MEDLINE PubMed search for articles published in English from January 1990 to January 2014 was completed using the terms: pharmacokinetics, colchicine, canakinumab, allopurinol, febuxostat, pegloticase, gout, toxicity, drug interaction. Expert opinion: Colchicine is a drug with a narrow therapeutic-toxicity window. Co-prescription with strong CYP3A4 or P-glycoprotein inhibitors can greatly modify its pharmacokinetics and is to be avoided. Elimination of canakinumab mainly occurs via intracellular catabolism, following receptor mediator endocytosis. Canakinumab appears to be a good alternative for patients with contraindications to colchicine, NSAIDs and corticosteroids. For patients with renal impairment, some authors recommend that the allopurinol maximum dosage should be adjusted to creatinine clearance. If the urate target cannot be achieved, the therapy should be switched to febuxostat, which is appropriate with mild–to-moderate renal failure. Anti-pegloticase antibodies affect the pharmacokinetics of the drug because they increase its clearance, with loss of pegloticase activity.